High-porosity and high-toughness boron nitride ceramic as well as preparation method and application thereof

By combining boron nitride whiskers with boron nitride porous materials, high porosity and high toughness boron nitride ceramics are prepared by sintering technology, which solves the problem of low porosity of existing ceramics, and achieves better mechanical properties and a wider application range.

CN119613142APending Publication Date: 2025-03-14SHANDONG JINGYI NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510046116.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The porosity of existing boron nitride ceramics is low, resulting in uneven densification during the sintering process, and problems such as bending and curling are encountered, making it difficult to meet the optimization requirements for pore structure and distribution in high-performance applications.

Method used

By combining boron nitride whiskers with boron nitride porous material and using a sintering process, a boron nitride ceramic material with high porosity and excellent toughness was prepared. The specific steps include selecting appropriate pore-forming agents, composite sintering aids and dispersants, and performing process processing such as ball milling, spray drying, cold pressing molding and high-temperature sintering.

Benefits of technology

It achieves the high porosity and excellent mechanical properties of boron nitride ceramics, improves its flexural strength and compressive strength, and broadens its application range in the field of high-performance electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613142A_ABST
    Figure CN119613142A_ABST
Patent Text Reader

Abstract

The invention provides high-porosity and high-toughness boron nitride ceramic as well as a preparation method and application thereof, and relates to the technical field of ceramic materials. The boron nitride ceramic is prepared from raw materials in parts by mass as follows: 100 parts of boron nitride powder, 4-7 parts of boron nitride whiskers, 5-15 parts of a pore forming agent, 3-8 parts of a composite sintering aid and 1-4 parts of a dispersing agent. The boron nitride ceramic with excellent porosity and mechanical properties is successfully prepared by combining the boron nitride whisker with the boron nitride porous material, reasonably adjusting the types and the ratio of the pore forming agent, the composite sintering aid and the dispersing agent and utilizing a sintering process. Compared with traditional boron nitride ceramics, the high-porosity boron nitride ceramic has the advantages that toughness and strength are not sacrificed while high porosity is kept, the application range of the high-porosity boron nitride ceramic in the fields of high-performance electronics and chemical industry is widened, and the high-porosity boron nitride ceramic has important technical value and market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a high-porosity and high-toughness boron nitride ceramic and a preparation method and application thereof. Background Art

[0002] Nitride ceramics are refractory compounds formed by the covalent bonding of nitrogen and metal or non-metal elements, and are widely used in many fields. Common nitride ceramics include silicon nitride (Si3N4), aluminum nitride (AlN) and boron nitride (BN). These ceramic materials have important applications in the fields of electronics, mechanics and thermal management due to their excellent properties. In particular, silicon nitride and aluminum nitride ceramics are widely used as ceramic substrates in electronic packaging due to their excellent hardness, mechanical strength and heat dissipation performance, showing huge market potential.

[0003] Boron nitride ceramics play an important auxiliary role in the preparation process of silicon nitride and aluminum nitride ceramics. As a substrate material, boron nitride ceramics can provide necessary support when sintering silicon nitride substrates or aluminum nitride substrates. Boron nitride ceramics have excellent properties such as high temperature resistance, low temperature impact resistance, and carbon corrosion resistance. Its maximum operating temperature can reach 2100°C, and it can maintain stable chemical properties in high temperature environments. It does not react with metal or ceramic materials and does not bond, so it has a long service life. In addition, boron nitride ceramics can also provide excellent chemical stability in high temperature or harsh environments, and are particularly suitable for applications that require corrosion resistance and long-term stable use.

[0004] In order to further improve the performance of boron nitride ceramics, it is usually required to have a certain porosity. The presence of pores can effectively absorb and conduct heat during the sintering process, promote the densification of the material, and help improve its thermal conductivity and heat dissipation performance. For the boron nitride substrate required for tape casting, a higher porosity can not only improve the thermal conductivity efficiency of the material, but also reduce the contact area between the material and the corrosive medium, thereby enhancing its chemical stability. In addition, high-porosity boron nitride ceramics show extremely excellent performance in heat dissipation. They can effectively conduct the heat generated by electronic devices and ensure the stable operation of electronic devices. This feature makes boron nitride ceramics widely used in thermal interface materials between high-performance chips and heat sinks, which can significantly reduce the temperature of electronic devices and improve the heat dissipation effect of circuit boards, thereby extending the service life of the equipment.

[0005] Conventional boron nitride substrates are usually prepared by hot pressing sintering process, but their porosity is low, which may lead to uneven densification of the sintered material when used as a setter, and then cause problems such as bending and warping. Therefore, how to optimize the pore structure and distribution while maintaining the excellent performance of the material has become the key to improving the performance of boron nitride substrates.

[0006] Boron nitride whiskers, as a fibrous single crystal, have a high aspect ratio, strength and thermal stability, and are often used as reinforcing fillers for polymer composites. Due to their excellent mechanical properties and high temperature and corrosion resistance, boron nitride whiskers are widely used to improve the strength and toughness of materials.

[0007] Therefore, it is of great application value to develop a method of combining the preparation of boron nitride whiskers with that of boron nitride porous materials and utilizing a sintering process to prepare a boron nitride ceramic material having high porosity and excellent toughness. Summary of the invention

[0008] The present invention aims to solve the problems existing in the prior art and provides a high-porosity and high-toughness boron nitride ceramic and its preparation method and application. The present invention combines the preparation of boron nitride whiskers with that of boron nitride porous materials and finally obtains a boron nitride ceramic material with high porosity and excellent toughness by sintering process, so as to provide better solutions in various high-performance applications.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] The first aspect of the present invention provides a high-porosity and high-toughness boron nitride ceramic, wherein the raw materials for its preparation include the following components by mass: 100 parts of boron nitride powder, 4-7 parts of boron nitride whiskers, 5-15 parts of pore formers, 3-8 parts of composite sintering aids, and 1-4 parts of dispersants.

[0011] Furthermore, the boron nitride whiskers are prepared according to the following method:

[0012] (a) adding boric acid and melamine to deionized water at 80-95° C. in sequence, wherein the mass ratio of boric acid to melamine is 11:7-11, heating the mixture to above 95° C., and keeping the mixture to react for 0.5-2 hours. After the reaction is completed, cooling the reactant to room temperature within 30 minutes to obtain a boron nitride whisker precursor;

[0013] (b) calcining the boron nitride whisker precursor at 1300-1700° C. for 1-3 h to obtain boron nitride whiskers.

[0014] Furthermore, the pore-forming agent is selected from one or more of urea, starch, naphthalene powder, carbon powder, diatom mud, polymethyl methacrylate, and methyl methacrylate.

[0015] Furthermore, the pore-forming agent is a mixture of starch, polymethyl methacrylate and urea, with a mass ratio of (4-6): (2-4): 1.

[0016] The present invention selects starch, polymethyl methacrylate and urea in a specific ratio as a pore-forming agent, wherein the gases generated by the decomposition of starch and urea in the low-temperature pre-sintering stage work together to form a large number of pores. During the low-temperature pre-sintering process, the gas generated by the decomposition of urea is mainly released in the medium-temperature stage, while the gas generated by the decomposition of starch is released in the lower temperature stage. The two complement each other, making the formation of pores more uniform. As the temperature further increases, polymethyl methacrylate begins to melt, and the liquid phase promotes the rearrangement of boron nitride powder, whiskers, and pores, so that the pores are evenly dispersed. Then, as the temperature further increases, polymethyl methacrylate also begins to decompose to form fine pores, further increasing the porosity of the ceramic. In addition, the hydroxyl groups in the starch molecules form hydrogen bonds with the surface of the boron nitride powder, which enhances the dispersibility of the powder. The polymethyl methacrylate molecules contain polar groups, which can interact with the surface of the boron nitride powder and reduce the agglomeration of the powders, thereby further improving the dispersibility of the powders. The gas produced by the decomposition of urea can further disperse the powder, making the powder particles more evenly distributed in the matrix.

[0017] Furthermore, the composite sintering aid is selected from one or more of yttrium oxide, magnesium oxide, zirconium oxide, aluminum oxide, silicon nitride, silicon oxide, and silicon carbide.

[0018] Furthermore, the composite sintering aid is a mixture of yttrium oxide, magnesium oxide and zirconium oxide in a mass ratio of (1-3):1:1.

[0019] The present invention selects a composite of yttrium oxide, magnesium oxide and zirconium oxide in a specific ratio as a sintering aid, wherein yttrium oxide can promote the growth and densification of the grains by reducing the surface energy and interface energy of the boron nitride grains, magnesium oxide promotes the rearrangement and densification of the grains by reducing the melting point of the boron nitride grains, and the addition of zirconium oxide can further refine the grains and improve the distribution of the grains. The synergistic effect of the three substances makes the grain structure of the boron nitride ceramic more optimized, thereby significantly improving the mechanical properties of the boron nitride ceramic.

[0020] Furthermore, the dispersant is selected from one or more of sodium lauryl sulfate, sodium metaaluminate, sodium stearate and citric acid.

[0021] The second aspect of the present invention provides a method for preparing the above-mentioned high-porosity and high-toughness boron nitride ceramic, comprising the following steps:

[0022] (1) mixing boron nitride powder, boron nitride whisker, pore former, composite sintering aid and dispersant according to mass ratio, and ball milling, wherein the ball milling medium is deionized water, the ball milling time is 10-15 hours, and the ball milling speed is 260-500 r / min;

[0023] (2) spray drying the ball-milled slurry to obtain a powder;

[0024] (3) adding the spray-dried powder into a mold, placing it into a cold isostatic pressing machine, and maintaining the pressure at 100-300 MPa for 60-120 seconds to obtain a cold pressed green body;

[0025] (4) placing the cold pressed green body into a crucible, heating it to 400-600° C., keeping it warm for a certain period of time, then introducing nitrogen, heating it to 1800-2000° C., keeping it warm for a certain period of time, and obtaining the high porosity and high toughness boron nitride ceramic.

[0026] Furthermore, step (4) is specifically as follows: placing the cold-pressed green body into a crucible, heating it to 400-600°C at a rate of 2-4°C / min, keeping it warm for 1-3h, then introducing nitrogen, heating it to 1800-2000°C at a rate of 4-6°C / min, keeping it warm for 1-3h, to obtain the high-porosity and high-toughness boron nitride ceramic.

[0027] Step (4) includes a low-temperature pre-sintering step before high-temperature sintering. This step helps to remove the residues of organic matter and pore-forming agent, and at the same time makes the powder particles initially bonded to form a certain strength. In this way, during the subsequent high-temperature sintering, the green body is not easy to deform and crack, which is beneficial to improve the densification degree and mechanical properties of the material.

[0028] The third aspect of the present invention provides the use of the above-mentioned high-porosity and high-toughness boron nitride ceramic in the preparation of electronic heat dissipation materials, electrical insulation materials, semiconductor devices, corrosion-resistant equipment, high-temperature reactors, and smelting equipment.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention provides a high-porosity and high-toughness boron nitride ceramic and a preparation method thereof. Boron nitride whiskers are combined with boron nitride porous materials and a boron nitride ceramic with excellent porosity and mechanical properties is successfully prepared by a sintering process. The present invention successfully optimizes the pore structure and distribution of the boron nitride ceramic by reasonably adjusting the types and ratios of pore formers, composite sintering aids and dispersants, thereby improving its flexural strength and compressive strength. Compared with traditional boron nitride ceramics, the present invention can maintain a relatively high porosity without sacrificing toughness and strength, broadening its application range in the field of high-performance electronics, and has important technical value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM image of the boron nitride whisker prepared in Example 1.

[0032] Figure 2 This is the SEM image of the boron nitride ceramic prepared in Example 2.

[0033] Figure 3This is the SEM image of the boron nitride ceramic prepared in Example 3.

[0034] Figure 4 The flexural strength and compressive strength of Examples 2-5 vary with porosity. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It is worth noting that the methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercially available products unless otherwise specified, and their sources are not specifically limited.

[0036] Example 1

[0037] This embodiment provides a method for preparing boron nitride whiskers, comprising the following steps:

[0038] (a) adding deionized water into a heating stirring pot, and after the water temperature rises to 90°C, adding boric acid and melamine in order, wherein the mass ratio of boric acid to melamine is 11:9, and the total mass of boric acid and melamine is 6% of deionized water, heating the stirring pot to above 95°C and keeping the temperature for 1 hour, then removing the top cover of the heating stirring pot, stopping heating, and then rapidly stirring to dissipate heat, cooling to room temperature within 30 minutes, and obtaining a boron nitride whisker precursor;

[0039] (b) The whisker precursor was placed in a tubular furnace for calcination at 1500°C for 2 h to obtain uniform boron nitride whiskers, as shown in the SEM image. Figure 1 shown.

[0040] Example 2

[0041] This embodiment provides a high-porosity and high-toughness boron nitride ceramic, the raw materials for its preparation include the following components by mass: 100 parts of boron nitride powder, 5 parts of boron nitride whiskers, 10 parts of pore formers, 3 parts of composite sintering aids, and 2 parts of dispersants;

[0042] Wherein, boron nitride whiskers are prepared according to the method of Example 1;

[0043] The pore-forming agent is a mixture of starch, polymethyl methacrylate, and urea in a mass ratio of 5:3:1;

[0044] The composite sintering aid is a mixture of yttrium oxide, magnesium oxide and zirconium oxide in a mass ratio of 5:3:3;

[0045] The dispersant is sodium dodecyl sulfate;

[0046] The preparation of the boron nitride ceramic comprises the following steps:

[0047] (1) Boron nitride powder, boron nitride whiskers, pore formers, composite sintering aids and dispersants were mixed according to mass ratios, and ball milled. The ball milling medium was deionized water. The ball milling time was 2 h and the ball milling speed was 360 r / min.

[0048] (2) spray drying the ball-milled slurry to obtain a powder;

[0049] (3) adding the spray-dried powder into a mold, placing it into a cold isostatic pressing machine, and maintaining the pressure at 200 MPa for 90 seconds to obtain a cold pressed green body;

[0050] (4) The cold-pressed green body is placed in a crucible, and the temperature is increased to 500°C at a rate of 3°C / min, and kept at this temperature for 2 hours. Then, nitrogen is introduced, and the temperature is increased to 1950°C at a rate of 5°C / min, and kept at this temperature for 2 hours to obtain the high-porosity and high-toughness boron nitride ceramic.

[0051] SEM images of boron nitride ceramics are shown below: Figure 2 As shown in the figure, it can be seen that there are many pores on the surface of the boron nitride ceramic, and boron nitride whiskers can be seen in the pores.

[0052] After testing, the density of the boron nitride ceramic prepared in Example 2 is 1.47 g / cm 3 The porosity is 38.8%, the flexural strength is 67.30MPa, and the compressive strength is 87.16MPa.

[0053] Example 3

[0054] This embodiment provides a high-porosity and high-toughness boron nitride ceramic, which differs from Embodiment 2 in that the pore-forming agent is 5 parts.

[0055] SEM images of boron nitride ceramics are shown below: Figure 3 As shown, pores and whiskers can be seen on the ceramic surface.

[0056] After testing, the density of the boron nitride ceramic prepared in Example 3 is 1.84 g / cm 3 The porosity is 21.9%, the flexural strength is 80.67MPa, and the compressive strength is 104.25MPa.

[0057] Example 4

[0058] This embodiment provides a high-porosity and high-toughness boron nitride ceramic, which differs from Embodiment 2 in that the pore-forming agent is 15 parts.

[0059] After testing, the density of the boron nitride ceramic prepared in Example 4 is 1.23 g / cm3 The porosity is 46.6%, the flexural strength is 43.98MPa, and the compressive strength is 58.34MPa.

[0060] Example 5

[0061] This embodiment provides a high-porosity and high-toughness boron nitride ceramic, which differs from Embodiment 2 in that 20 parts of pore-forming agent are used.

[0062] After testing, the density of the boron nitride ceramic prepared in Example 5 is 1.11 g / cm 3 The porosity is 57.4%, the flexural strength is 27.54MPa, and the compressive strength is 41.28MPa.

[0063] The bending strength and compressive strength of the boron nitride ceramics prepared in Example 2-5 vary with porosity. Figure 4 As shown, it can be seen that with the increase of the porosity of the sample, its flexural strength and compressive strength show a decreasing trend.

[0064] Comparative Example 1

[0065] This comparative example provides a boron nitride ceramic, and the preparation method thereof comprises the following steps:

[0066] (1) 100 parts of boron nitride powder and 3 parts of a composite sintering aid (yttrium oxide and magnesium oxide in a mass ratio of 5:3) were mixed and ball-milled for 12 hours using deionized water as the ball-milling medium at a speed of 360 r / min;

[0067] (2) drying the ball-milled slurry in an oven at 80°C and then passing it through a 100-mesh sieve for later use;

[0068] (3) Add the dried powder into a mold, place it in a cold isostatic pressing machine, and form it under a pressure of 200 MPa for 90 seconds to obtain a cold pressed green body;

[0069] (4) After the cold-pressed green body is processed and trimmed, it is placed in a graphite mold and sintered under nitrogen atmosphere protection at 5°C / min and kept at 1950°C for 2h to obtain boron nitride ceramics.

[0070] The density of the boron nitride ceramic prepared in this comparative example is 2.03 g / cm 3 , the porosity is 8.6%, the flexural strength is 22.5MPa, and the compressive strength is 27.05MPa.

[0071] Comparative Example 2

[0072] This comparative example provides a boron nitride ceramic, which differs from Example 2 in that, in step (4), the cold-pressed green body is placed in a crucible, nitrogen is introduced, the temperature is increased to 1950° C. at a rate of 5° C. / min, and the temperature is maintained for 2 hours to obtain the boron nitride ceramic.

[0073] After testing, the density of the boron nitride ceramic prepared in this comparative example is 1.52g / cm 3 The porosity is 26.7%, the flexural strength is 37.2MPa, and the compressive strength is 54.8MPa.

[0074] Comparative Example 2 lacks a low-temperature pre-sintering step, and the pore-forming agent is incompletely or unevenly decomposed during the high-temperature sintering process, resulting in an uneven pore structure, large pores, and pore aggregation. These defects will become stress concentration points, which are easy to cause the initiation and expansion of cracks under the action of external forces, thereby reducing the bending strength and compressive strength of the material. In addition, due to the lack of a low-temperature pre-sintering step, the grains in Comparative Example 2 grow excessively or aggregate during the high-temperature sintering process, resulting in uneven grain distribution, thereby affecting the strength and toughness of the material.

[0075] Comparative Example 3

[0076] This comparative example provides a boron nitride ceramic, which differs from Example 2 in that the pore-forming agent is starch.

[0077] The density of the boron nitride ceramic prepared in this comparative example is 1.61 g / cm 3 , the porosity is 23.1%, the flexural strength is 29.2MPa, and the compressive strength is 20.2MPa.

[0078] In Comparative Example 3, only starch is used as a pore-forming agent. The decomposition temperature of starch is much lower than the sintering temperature. During the pre-sintering process, the gas produced by the decomposition of starch may be rapidly released at a lower temperature stage, resulting in uneven pore formation. It is easy to form larger pores when the temperature is further increased, and even cause pore aggregation. These defects will become stress concentration points, which can easily cause the initiation and expansion of cracks under the action of external forces.

[0079] Comparative Example 4

[0080] This comparative example provides a boron nitride ceramic, which differs from Example 2 in that the sintering aid is yttrium oxide.

[0081] After testing, the density of the boron nitride ceramic prepared in this comparative example is 1.32g / cm 3 The porosity is 40.6%, the flexural strength is 32.1MPa, and the compressive strength is 43.8MPa.

[0082] In Comparative Example 4, only yttrium oxide was used as a sintering aid. Although single yttrium oxide can reduce the sintering temperature of boron nitride ceramics and promote densification to a certain extent, its effect is limited. It is far inferior to the composite sintering aid of Example 2 in promoting grain growth, densification and homogenization.

[0083] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A high-porosity and high-toughness boron nitride ceramic, wherein the raw materials for its preparation include the following components by mass: 100 parts of boron nitride powder, 4-7 parts of boron nitride whiskers, 5-15 parts of pore formers, 3-8 parts of composite sintering aids, and 1-4 parts of dispersants.

2. The high porosity and high toughness boron nitride ceramic according to claim 1, characterized in that: The boron nitride whiskers are prepared as follows: (a) adding boric acid and melamine to deionized water at 80-95° C. in sequence, wherein the mass ratio of boric acid to melamine is 11:7-11, heating the mixture to above 95° C., and keeping the mixture to react for 0.5-2 hours. After the reaction is completed, cooling the reactant to room temperature within 30 minutes to obtain a boron nitride whisker precursor; (b) calcining the boron nitride whisker precursor at 1300-1700° C. for 1-3 h to obtain boron nitride whiskers.

3. The high porosity and high toughness boron nitride ceramic according to claim 1, characterized in that: The pore-forming agent is selected from one or more of urea, starch, naphthalene powder, carbon powder, diatom mud, polymethyl methacrylate, and methyl methacrylate.

4. The high porosity and high toughness boron nitride ceramic according to claim 3, characterized in that: The pore-forming agent is a mixture of starch, polymethyl methacrylate and urea, with a mass ratio of (4-6): (2-4):

1.

5. The high porosity and high toughness boron nitride ceramic according to claim 1, characterized in that: The composite sintering aid is selected from one or more of yttrium oxide, magnesium oxide, zirconium oxide, aluminum oxide, silicon nitride, silicon oxide, and silicon carbide.

6. The high porosity and high toughness boron nitride ceramic according to claim 1, characterized in that: The composite sintering aid is a mixture of yttrium oxide, magnesium oxide and zirconium oxide, with a mass ratio of (1-3):1:

1.

7. The high porosity and high toughness boron nitride ceramic according to claim 1, characterized in that: The dispersant is selected from one or more of sodium lauryl sulfate, sodium metaaluminate, sodium stearate and citric acid.

8. The method for preparing the high-porosity and high-toughness boron nitride ceramic according to any one of claims 1 to 7 comprises the following steps: (1) mixing boron nitride powder, boron nitride whisker, pore former, composite sintering aid and dispersant according to mass ratio, and ball milling, wherein the ball milling medium is deionized water, the ball milling time is 10-15 hours, and the ball milling speed is 260-500 r / min; (2) spray drying the ball-milled slurry to obtain a powder; (3) adding the spray-dried powder into a mold, placing it into a cold isostatic pressing machine, and maintaining the pressure at 100-300 MPa for 60-120 seconds to obtain a cold pressed green body; (4) placing the cold pressed green body into a crucible, heating it to 400-600° C., keeping it warm for a certain period of time, then introducing nitrogen, heating it to 1800-2000° C., keeping it warm for a certain period of time, and obtaining the high porosity and high toughness boron nitride ceramic.

9. The preparation method according to claim 8, characterized in that: Step (4) is specifically as follows: placing the cold-pressed green body into a crucible, heating it to 400-600°C at a rate of 2-4°C / min, keeping it warm for 1-3h, then introducing nitrogen, heating it to 1800-2000°C at a rate of 4-6°C / min, keeping it warm for 1-3h, and obtaining the high-porosity and high-toughness boron nitride ceramic.

10. Use of the high-porosity and high-toughness boron nitride ceramics according to any one of claims 1 to 7 in the preparation of electronic heat dissipation materials, electrical insulation materials, semiconductor devices, corrosion-resistant equipment, high-temperature reactors, and smelting equipment.

Citation Information

Cited By

  • High-reflectivity multilayer ceramic substrate and preparation method thereof

    CN120698768A